(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to analyze the impact of diversifying the bank loan portfolio on the financial performance of the banks in the research sample. The research community was represented by commercial banks listed on the Iraq Stock Exchange, while the research sample was represented by (3 banks) chosen from among (19) banks listed on the Iraq Stock Exchange in the year (2014), which matched the research requirements for the period (2014-2021) using annual data. The Shannon Entropy (SE) index was used to measure the diversification of the bank loan portfolio, while financial performance was measured through several metrics, namely (capital owned to deposits, return on equity, cash to assets ratio), The statistical program (Excel), (Spss), and (Eviews V.9) was relied upon, The research found that most of the banks in the research sample focused their loans excessively on the commercial sector, There is a positive effect of diversifying the loan portfolio on the ratio of owned capital to deposits of the banks in the research sample as a whole, While there is a negative effect of diversifying the loan portfolio on the cash-to-assets ratio of the banks in the research sample combined